Antipredator strategies of striped skunks in response to cues of aerial and terrestrial predators. (September 2018) - Fisher, Kimberly A.; Stankowich, Theodore
Abstract : Prey species defend themselves behaviourally and morphologically, and often use varied antipredator strategies against dissimilar predator types (i.e. terrestrial versus aerial). Striped skunks, Mephitis mephitis, spray noxious secretions at predators and advertise this danger with deterrent behaviours and black-and-white aposematic coloration. Evidence suggests skunks are effective at deterring terrestrial mammalian predators but are vulnerable to aerial predators; how skunks assess the risk posed by different predator types, however, has not been examined empirically. We recorded the behavioural responses of skunks to audio playbacks of coyotes, Canis latrans, and great horned owls, Bubo virginianus (the primary terrestrial and aerial predators of skunks, respectively), and peregrine falcons, Falco peregrinus, and white noise as controls. Skunks ran away more often from vocalizations of their main predators, great horned owls and coyotes, than from diurnal falcon vocalizations or white noise recordings. Skunks also tended to run away sooner in response to owl vocalizations than falcon or coyote vocalizations. Finally, subjects tended to engage in vigilance more frequently in response to owl vocalizations than in response to coyote vocalizations, which together with other results suggest that skunks may perceive owls as more threatening relative to coyotes. This study elucidates how a well-defended mammal can determine which perceived threat is the riskiest and alter its behaviour when its main defence strategy may not be successful against all predator types. Highlights: Skunk defences were more effective against mammalian predators than avian predators. Skunks fled sooner and more often from great horned owl calls than from coyote calls. Owls may be perceived as more threatening than coyotes. Skunk responses to a predator varies based on the predator's relative threat.